Identification of organic species with "double-sided tape" characteristics on the surface of carbonate reservoir rock. (15th March 2021) - Tessarolo, Nathalia; Wang, Nan; Wicking, Chrissie; Collins, Ian; Webb, Kevin; Couves, John; Crouch, Jonathan; Durkan, Colm; Zeng, Huang
Graphic abstract: Highlights: The organic compounds covering the surface of carbonate reservoir rock have been obtained by sequential extraction. The organic species strongly bound to carbonate reservoir rock are dominated by molecules like "double-sided tape". The discovery was further supported by AFM studies. The results provide highly useful clues to design new EOR methods for carbonate reservoirs. Abstract: Carbonate reservoir rocks are normally mixed-wet or oil-wet, leading to low oil recovery efficiency using water-based oil recovery methods. It is critical to understand the molecular composition of the organic material coating the surface of carbonate reservoir rock in order to design better enhanced oil recovery (EOR) methods. Herein, we extracted organic compounds from a carbonate reservoir rock and characterized their composition using high resolution mass spectrometry (HRMS). In contrast to conventional interpretation that the mixed-wet or oil-wet nature of carbonate reservoir rocks arises from the adsorption of carboxylic acids, our results demonstrated that the organic species strongly bound to carbonate reservoir rock surface are dominated by N-containing species, including a group of "sticky molecules". Each of these molecules can form multiple hydrogen-bonds, therefore they might act as a "double-sided tape" which binds crude oil strongly to the carbonate rock surface. Furthermore, we applied atomic force microscopy (AFM) techniques to a model mineral surface with regions of positive change and negative charge which was contacted with the crude oil produced from the formation where the rock was sampled. It was found that only the organic molecules with positive charge in the oil were adsorbed onto the mineral. This supports HRMS results which suggest that the organic materials strongly bound to the carbonate reservoir rock surface are dominated by basic N-containing molecules. Overall, these findings suggest that, beside fatty acids, these "sticky molecules" might also play an important role in controlling the wetting state of carbonate reservoir rock.